Bond behavior of cleaned corroded rebar repaired by partial depth repair. (October 2020) - Alabduljabbar, Hisham; West, Jeffrey
Abstract: This study investigated the bond behavior of reinforced concrete members subjected to corrosion and rehabilitated by partial depth repair using self-compacting concrete. Twelve beam-end specimens (600 × 500 × 250 mm) were tested, and two bonded lengths were considered (250 mm and 350 mm) to study the bond behavior of cleaned corroded rebar repaired by partial depth repair concrete. Two levels of corrosion were studied (5% and 10%) and were compared with control specimens (non-corroded specimens). A commercial prepacked self-compacting concrete (SCC) was used as the partial depth repair concrete and was compared to monolithic normal concrete (MNC) specimens. The bond stress-slip behavior was assessed using three linear variable differential transformers (LVDTs). Two LVDTs were placed at the loaded end of the rebar, and a third was placed at the free end, to measure the free-end slip. Generally, for the same bonded length, the average bond strength of the repaired clean rebar increased as the corrosion level increased. As the bonded length increased from 250 mm to 350 mm, the average bond strength decreased, and the corresponding bar slip increased. The beam-end specimens with the 250 mm bonded length failed by splitting of the concrete. However, the failure mode of the beam-end specimens with the 350 mm bonded length was a combination of pull-out and splitting failure or bar yield and splitting failure.